2020
DOI: 10.3389/fbioe.2020.00796
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Human Dental Pulp and Endothelial Cell Seeded Tyrosine-Derived Polycarbonate Scaffolds for Robust in vivo Alveolar Jaw Bone Regeneration

Abstract: The ability to effectively repair craniomaxillofacial (CMF) bone defects in a fully functional and aesthetically pleasing manner is essential to maintain physical and psychological health. Current challenges for CMF repair therapies include the facts that craniofacial bones exhibit highly distinct properties as compared to axial and appendicular bones, including their unique sizes, shapes and contours, and mechanical properties that enable the ability to support teeth and withstand the strong forces of mastica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In this case, cellular scaffolds showed more homogeneous bone formation and vascularization when compared to defects grafted with acellular scaffolds. 55 Further research showed that hDPSCs seeded on PCL/BCP scaffolds and then implanted into rabbit cranial CSDs promoted bone formation and maturation. 246 5III).…”
Section: Stem Cells As a Source Of Bioactive Molecules For Enhancing ...mentioning
confidence: 99%
“…In this case, cellular scaffolds showed more homogeneous bone formation and vascularization when compared to defects grafted with acellular scaffolds. 55 Further research showed that hDPSCs seeded on PCL/BCP scaffolds and then implanted into rabbit cranial CSDs promoted bone formation and maturation. 246 5III).…”
Section: Stem Cells As a Source Of Bioactive Molecules For Enhancing ...mentioning
confidence: 99%
“…Notably, HDPC seeded scaffolds strongly expressed dentin sialophosphoprotein, along with osteocalcin and angiogenic marker F8, which was found absent in acellular scaffolds after 3 months of implantation. 161 Recently, Saxena et al investigated craniomaxillofacial bone regeneration in an E1001(1k) scaffold, incorporated with dicalcium phosphate dihydrate (DCPD), an osteoconductive coating to overcome the limitations of traditionally used BGS. Herein, the fabricated E1001(1k)/DCPD, E1001(1k)/β-TCP, and E1001(1k) scaffolds showed bimodal porous structures with interconnected micro-and macropores.…”
Section: Tissue Engineering and Regenerative Medicine 421 Bone Tissuementioning
confidence: 99%
“…(iv) Rabbit mandible defect model created by drilling the buccal cortex, and the subsequent replacement with E1001­(1k)/β-TCP scaffolds. Reprinted with permission under a Creative Commons (CC-BY 4.0) License from ref . Copyright 2020 Frontiers Media S.A.…”
Section: Biomedical Applications Of Tyrosine-derived Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a mandibular distraction model in New Zealand white rabbits, Alkaisi et al showed that SHED can significantly enhance mandibular distraction osteogenesis (DO) (79). Most recently, Zhang et al showed that transplantation of hDPSC/endothelial cells (HUVEC)seeded E1001(1K)/β-TCP scaffolds significantly enhance bone formation in critical-sized alveolar bone defects in an in vivo rabbit mandible defect model (77). Gutiérrez-Quintero reported that transplantation of DPSCs seeded with hydroxyapatite matrix and polylactic polyglycolic acid (HA/PLGA) scaffolds also significantly augmented bone regeneration in bilateral mandibular critical-sized defects in rabbits (78) (96).…”
Section: Dental Pulp Stem Cells (Dpscs) and Stem Cells From Human Exfoliated Deciduous Teeth (Shed)mentioning
confidence: 99%